Advances in the understanding and management of histiocytic disorders 2015. Issue 2 (February 2016) - Windebank, Kevin; Visser, Johannes; Nanduri, Vasanta
Abstract: Childhood histiocytoses encompass a range of illnesses that can present with a skin rash or single bony lesion that may spontaneously regress, or result in a systemic disease leading to multiorgan failure and death. For practical purposes they can be classified into four groups: Langerhans Cell Histiocytosis (LCH), Non-Langerhans Cell Histiocytoses (Non-LCH), Haemophagocytic Lymphohistiocytoses (HLH) and Histiocyte Lineage-related Malignancies. The establishment of diagnostic, staging and response criteria for LCH has enabled a series of international, randomised clinical trials that are the foundation of current evidence based treatment. Most cases respond to treatment but some children are left with significant permanent consequences affecting the skeleton and endocrine system. Cases of non-LCH are often difficult to diagnose and manage and require expert advice. Familial HLH is an inherited disease in which initial remission can be gained by chemotherapeutic or immunological strategies, but then requires allogeneic stem cell transplant for cure. There are a variety of leukaemias and sarcomas that are phenotypically derived from the histiocytic lineage. This article reviews the presenting features of histiocytic diseases and outlines current treatment regimes.